Mutual Sense-Censoring, Generative Exploration, and Collaborative Change: A Case Study of Headquarters–Subsidiary Relationships in Asia. - Nagaishi, Makoto (Journal of Applied Behavioral Science, 2025)
This study contributes to the literature on power processes within multinational corporations (MNCs) by finding that the headquarters and subsidiaries mutually censor their sensemaking and may opt for strategic in action, depending on the relational context. It develops systematic explanations of the patterns in the headquarter–subsidiary partnership by proposing a model of evolutionary, co-existent meaning-making transition processes. In a Japanese manufacturing MNC, change practitioners helped balance paradoxical processes to create psychological safety in a dialogic space, leading members to move ahead with a sense of crisis. The study deals with collective reactions to change from a qualitatively grounded approach. It then proposes theoretical and practical implications for building collaboration capability in multistakeholder partnerships by inspiring people's spirit of inquiry.